Agricultural production structure and inequality of educational development in China - Wei, Jingzhou; Yu, Yawen (Frontiers in Psychology, 2022)
Unbalanced regional development in China has always been the focus of the government's attention. Agricultural development in China's main agricultural regions is characterised by relatively obvious features, which are mainly manifested in the excessive concentration of agricultural production on one crop or a few agricultural products. Whether this trend of concentration will help to improve the inequalities in China's educational development is an important question for this study. Based on China's population, education and agricultural data over the past 20 years, this paper provides an in-depth analysis of educational inequalities in five typical agricultural-producing provinces by calculating indicators such as the rationalisation index of agricultural production structures, the average number of years of schooling of residents and the Gini coefficient of education, in order to analyze the essential reasons for the development of education inequality in major agricultural producing areas. The results show that the urban-rural gap is an important factor affecting the equality of educational development in the main agricultural production areas; the reduction of the rationalization index of agricultural production structure can promote the improvement of inequality in educational development and narrow the urban-rural educational development gap; it also shows that the improvement of specialization in major agricultural producing areas is conducive to reducing educational inequality in major agricultural producing provinces; these conclusions provide a useful reference for narrowing the urban-rural education gap in the main agricultural production areas.